ISLAM AND SOCIAL RECONSTRUCTION IN THE MULTICULTURAL SOCIETY OF BUGIS-SASAK FISHERMEN IN MANDAR VILLAGE, EAST LOMBOK REGENCY - Muhammad Dimas Hidayatullah Wildan (Universitas Islam Negeri Mataram, 2025)
This study aims to examine the role of Islam in the process of social reconstruction among the multicultural communities of Bugis and Sasak fishermen in Mandar Hamlet, Seruni Mumbul Village, Pringgabaya District, East Lombok Regency. The method used is qualitative research with a sociological approach. The results of the study show that Islamic teachings are a strong foundation in building harmonious social relations between the Bugis and Sasak communities. Religious traditions, joint religious studies, and customary activities combined with Islamic values ??are important media in the process of social reconstruction, including in resolving conflicts, strengthening cross-cultural solidarity, and active participation in the development of fishing communities.